Contribution to the Lepidoptera fauna of the Madeira Islands. Part 2. Tineidae, Acrolepiidae, Epermeniidae. - Gaedike, Reinhard; Karsholt, Ole (Contributions to Entomology = Beiträge zur Entomologie, 2001)
A review of three families Tineidae, Epermeniidae and Acrolepiidae in the Madeira Islands is given. Three new species: Monopis henderickxi sp. n. (Tineidae), Acrolepiopsis mouli sp. n. and A. infundibulosa sp. n. (Acrolepiidae) are described, and two new combinations in the Tineidae: Ceratobia oxymora (Meyrick) comb. n. and Monopis barbarosi (Koçak) comb. n. are listed. Trichophaga robinsoni nom. n. is proposed as a replacement name for the preoccupied T. abruptella (Wollaston, 1858). The first record from Madeira of the family Acrolepiidae (with Acrolepiopsis vesperella (Zeller) and the two above mentioned new species) is presented, and three species of Tineidae: Stenoptinea cyaneimarmorella (Millière), Ceratobia oxymora (Meyrick) and Trichophaga tapetzella (Linnaeus) are reported as new to the fauna of Madeira. The Madeiran records given for Psychoides filicivora (Meyrick) are the first records of this species outside the British Isles. Tinea pellionella Linnaeus, Monopis laevigella (Denis & Schiffermüller) and M. imella (Hübner) are deleted from the list of Lepidoptera found in Madeira. All species and their genitalia are figured, and information on bionomy is presented.KeywordsMadeira, Microlepidoptera, Tineidae, Epermeniidae, Acrolepiidae, Laurisilva.Nomenclatural Actsinfundibulosa Gaedike & Karsholt, 2001 (Acrolepiopsis), spec. n.mauli Gaedike & Karsholt, 2001 (Acrolepiopsis), spec. n.oxymora (Meyrick, 1919) (Ceratobia), comb. n. hitherto Tinea oxymorabarbarosi (Koçak, 1981) (Monopis), comb. n. hitherto Reisserita barbarosihenderickxi Gaedike & Karsholt, 2001 (Monopis), spec. n.robinsoni Gaedike & Karsholt, 2001 (Trichophaga), nom. n. pro Trichophaga abruptella Wollaston, 1858, nec Thunberg, 1794